Expression Profiles of Antimicrobial Peptides in the Genital Tract of Women Using Progesterone Intrauterine Devices Versus Combined Oral Contraceptives. (2nd August 2014) - Introini, Andrea; Kaldensjö, Tove; Hirbod, Taha; Röhl, Maria; Tjernlund, Annelie; Andersson, Sonia; Broliden, Kristina
<x xml:space="preserve">Abstract</x> Problem Sex hormones can influence the immune defenses of the female genital tract (FGT) and its susceptibility to infections. Here we investigated the effect of different hormonal contraceptives on the production of antimicrobial peptides (AMPs) in different compartments of the female genital mucosa (FGM), secretions and tissue. Method of study Cervicovaginal secretions (CVS) and ectocervical tissue samples obtained from women using progesterone intrauterine devices (pIUD) (n = 23) and combined oral contraceptives (COC) (n = 23) were analyzed for the expression and in situ localization of HNP1‐3, BD‐2, LL‐37, SLPI and trappin‐2 by ELISA, real‐time PCR and immunohistochemistry. Results Women using COC had significantly lower mRNA levels of BD‐2 and trappin‐2 in ectocervical tissue than pIUD users. The two groups showed no differences in CVS concentration, as well as similar in situ expression patterns in ectocervical tissue, of all five AMPs. Conclusions The use of hormonal contraceptives influences AMP expression differently in genital secretions compared to ectocervical tissue. This suggests that the impact of sex hormones on local immune defenses varies in different compartments of the FGM, and likely in different locations across the FGT.